Adaptive Pid Control With Pitch Moment Rejection For Reducing Unwanted Vehicle Motion In Longitudinal Directionle - Ahmad, Fauzi; Hudha, Khisbullah; Jamaluddin, Hishamuddin (Journal of Mechanical Engineering and Technology (JMET), 2010)
This manuscript provides a detailed derivation of a full vehicle model, which may be used to simulate the behavior of a vehicle in longitudinal direction. The dynamics of a 14 degrees of freedom (14-DOF) vehicle model are derived and integrated with an analytical tire dynamics namely Calspan tire model. The full vehicle model is then validated experimentally with an instrumented experimental vehicle based on the driver input from brake or throttle pedals. Several transient handling tests are performed, namely sudden acceleration and sudden braking test. Comparisons of the experimental result and model response with sudden braking and throttling imposed motion are made. The results of model validation show that the trends between simulation results and experimental data are almost similar with acceptable error. An adaptive PID control strategy is then developed on the validated full vehicle model to reduce unwanted vehicle motions during sudden braking and throttling maneuver. The results show that the proposed control structure is able to significantly improve the dynamic performance of the vehicle during sudden braking and sudden acceleration under various conditions. The proposed controller will be used to investigate the benefits of a pneumatically actuated active suspension system for reducing unwanted vehicle motion in longitudinal direction